Economic‐Development Stakeholder Perspectives on Boomtown Dynamics in the Eagle Ford Shale, Texas1. Issue 1 (17th November 2016) - Murphy, Trey; Brannstrom, Christian; Fry, Matthew; Ewers, Michael
Abstract: Unconventional oil and gas production in the United States reversed a decades‐old trend of rising oil imports, provided an argument for lifting the U.S. crude oil export ban and motivated the development of domestic natural gas export facilities. But the most visible impact of unconventional‐hydrocarbon extraction is the creation of boomtowns in rural regions. Despite widespread media coverage, scholarly analysis of boomtowns is restricted to regional econometric studies with little attention to how economic stakeholders understand and respond to booming economies. Here we analyze interviews with key economic stakeholders in the Eagle Ford Shale in Texas. Respondents consider their community's economic success relative to the price of oil and indicate concerns about the deterioration of roads, high housing demand, and skyrocketing wages. We also re‐examine John Gilmore's foundational work on boomtowns in the 1970s in the context of contemporary unconventional extraction.